Factors Affecting Health Worker Anxiety in Covid-19 Prevention at Murni Teguh Memorial Hospital - Lilies Lingkaran; Sri Lestari Ramadhani Nasution; Ermi Girsang; Chrismis Novalinda Ginting (International Journal of Health and Pharmaceutical (IJHP), 2022)
The incidence of Covid-19 is a pandemic that has hit the whole world. Health workers who treat Covid-19 patients are a group with a very high risk of exposure. The psychological response experienced by health workers to infectious disease pandemics is increasing because it is caused by feelings of anxiety. This study analyzes what factors influence the anxiety of health workers in preventing Covid-19 at Murni Teguh Memorial Hospital. This research is a quantitative analytic study with a cross sectional approach. The research population is health workers who are limited to doctors and nurses who are tasked with preventing, handling and caring for Covid-19 patients in the emergency room installation and isolation room at Murni Teguh Memorial Hospital Medan. Samples were taken using the Taro Yamane formula as many as 61 people. Methods of data collection through the distribution of questionnaires and documentation. The data analysis method consisted of univariate, bivariate and multivariate using multiple logistic regression equations. The results of the study showed the influence of workload, community stigma, family status, knowledge and availability of personal protective equipment (PPE) for health workers' anxiety in preventing Covid-19 in the Emergency Room and Pure Isolation Room of Teguh Memorial Hospital. The conclusion of the study is that the factors that influence the anxiety of health workers are workload, community stigma, family status, knowledge about Covid-19 prevention and the availability of PPE and workload is the dominant variable affecting the anxiety of health workers.